Zad.1Oblicz wartość wyrażenia ,gdy:a=3,b=7,c=1.
a)a+b b)2a+b
c)2a+c
d)2b-3a
e)4c-a
f)a+b-3c
g)2a-b+3c
h)2b-2a-2c
i)2(a+b+c)
Zad.2
a)3x-2-2x+5+4x, gdy x = 12
b)3a-b+5a+2b-6, gdy a=2 i b=2
c)x+2y-3y-3z+5z-x, gdy x=1,y=8,z=6
d)3(x-4z+y+4x-z+2y), gdy x=1,y=2,z=12

3

Odpowiedzi

2010-02-15T16:17:19+01:00
A-10
b-13
c-7
d-11
e-1
f-7
g-2
h-6
i-22

a-58
b-12
c-4
d-53
2010-02-15T16:27:25+01:00
Zad.1
a) a + b odp 3+7=10
b)2a+b odp 2razy 3 + 7= 6+7=13
c)2a+c odp 2 razy 3 +1 = 6+1 =7
d)2b-3a odp. 2 razy 7-3 razy 3= 14-9=5
e)4c-a odp. 4 razy 1-3=4-3=1
f)a+b-3c odp. 3+7-3razy 1= 10-3=7\
g)2a-b+3c odp. 2 razy 3 -7+3 razy 1=6-7+3=2
h)2b-2a-2c odp. 2 razy7- 2 razy 3-2razy 1=14-6-2=6
i)2(a+b+c) odp. 2razy a + 2 razy b + 2 razy c= 2 razy3 + 2 razy 7+ 2 razy 1= 6+14+2=22
zad.2
1 5 1
Najlepsza Odpowiedź!
2010-02-15T16:28:25+01:00
Zad.1
a) 3+7=10
b) 2*3+7=13
c) 2*3+1=7
d) 2*7-3*3=14-9=5
e) 4*1-3=4-3=1
f) 3+7-3*1=3+7-3=10-3=7
g) 2*3-7+3*1=5-7+3=2
h) 2*7-2*3-2*1=14-6-2=6
i) 2*(3+7+1)=2*11=22

Zad. 2
a) 5x+3=5*12+3=60+3=63
b) 8a+1b-6=8*2+1*2-6=16+2-6=18-6=12
c) -1y+8z=-1*8+8*6=-8+48=40
d) 3(5x+3z+3y)=3(5*1+3*12+3*2)=3(5+36+6)=3*47=141


Licze na najlepszą :)